Effects of climate on fall migration phenology of monarch butterflies departing the northeastern breeding grounds in Canada. Issue 8 (13th January 2023) - Ethier, Danielle M.; Mitchell, Greg W.
Abstract: Monarch butterflies ( Danaus plexippus ) undergo an iconic multi‐generational migration, traveling thousands of kilometers from the summer breeding grounds in southern Canada to overwintering sites in central Mexico. This migration phenomena can be affected by climate change, which may have important implications on fitness and ultimately populations status. We investigated the long‐term trends in fall migration phenology of monarchs using a 25‐year dataset collected along the coast of Lake Erie in Ontario, Canada. We also investigated local long‐term trends in weather covariates that have the potential to influence migration phenology at this site. Patterns in standardized daily counts of monarchs were compared with local weather covariates using two methods (i.e., monthly averages and moving windows) to assess difference in outputs between analytical approaches. Our results suggest that monarch migration timing (migration midpoint, average peak, first peak, and late passage) and weather covariates have been consistent over time, in direct contrast to a similar study in Cape May, New Jersey, which showed a significant increase in both fall temperature and a 16‐ to 19‐day shift in monarch migration timing. Furthermore, our results differed between analytical approaches. With respect to annual variability in air temperature, our monthly average analysis suggested that for each degree increase in September air temperature, late season passage would advance 4.71 days (±1.59 SE, p = .01). However, the moving window analysis suggested that this result is likely spurious and found no significant correlations between migration timing and any weather covariates. Importantly, our results caution against extrapolating the effects of climate change on the migration phenology of the monarch across study regions and the need for more long‐term monitoring efforts to better understand regional drivers of variability in migration timing. Abstract : Monarch butterflies ( Danaus plexippus ) migration timing can be affected by climate change. We investigated long‐term trends in fall migration phenology of monarchs using a 25‐year dataset collected in Ontario, Canada. Our results suggest that monarch migration timing and weather covariates have been consistent over time, in direct contrast to a similar study in Cape May, New Jersey. Our results caution against extrapolating the effects of climate change on the migration phenology of the monarch across study regions and the need for more long‐term monitoring efforts to better understand regional drivers of variability in migration timing.